Kolaborasi Orang Tua Dan Guru Bimbingan Konseling (BK) Dalam Mendukung Perkembangan Siswa Di MA Aisyiyah 1 Palembang - Imelda, Ovi; Akhmad Saputra, Ade (Transformation of Islamic Management and Education, 2025)
This study aims to analyze the role of collaboration between guidance and counseling (GC) teachers and parents in supporting student development at Madrasah Aliyah Aisyiyah 1 Palembang. The focus of this research is to identify the benefits of structured collaboration in helping both parties understand students' needs, as well as to determine improvement steps that should be taken to ensure students' future success. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews and observation, then analyzed using thematic analysis techniques. The findings indicate that collaboration between GC teachers and parents has a significant positive impact on students' emotional development, self-confidence, and social skills. However, the study also reveals several obstacles that hinder the effectiveness of such collaboration, including parents' time constraints, a lack of understanding about the role of GC teachers, and limited communication. Therefore, the study recommends more flexible meeting schedules, the use of technology to facilitate communication, and more intensive outreach to parents regarding the role of GC teachers. The implications of this research highlight the need for programs aimed at increasing parental involvement in their children's education and strengthening the partnership between school and family. For future research, it is recommended to use a mixed-methods approach (quantitative and qualitative) to gain a more comprehensive understanding of the collaboration between GC teachers and parents.